Accuracy and safety of ward based pleural ultrasound in the Australian healthcare system. Issue 3 (2nd November 2016) - Hammerschlag, Gary; Denton, Matthew; Wallbridge, Peter; Irving, Louis; Hew, Mark; Steinfort, Daniel
ABSTRACT: Background and objective: Ultrasound has been shown to improve the accuracy and safety of pleural procedures. Studies to date have been performed in large, specialized units, where pleural procedures are performed by a small number of highly specialized physicians. There are no studies examining the safety and accuracy of ultrasound in the Australian healthcare system where procedures are performed by junior doctors with a high staff turnover. Methods: We performed a retrospective review of the ultrasound database in the Respiratory Department at the Royal Melbourne Hospital to determine accuracy and complications associated pleural procedures. Results: A total of 357 ultrasounds were performed between October 2010 and June 2013. Accuracy of pleural procedures was 350 of 356 (98.3%). Aspiration of pleural fluid was successful in 121 of 126 (96%) of patients. Two (0.9%) patients required chest tube insertion for management of pneumothorax. There were no recorded pleural infections, haemorrhage or viscera puncture. Conclusion: Ward‐based ultrasound for pleural procedures is safe and accurate when performed by appropriately trained and supported junior medical officers. Our findings support this model of pleural service care in the Australian healthcare system. Abstract : Thoracic physician performed ultrasound has been shown to be safe and effective. We perform a retrospective review of pleural procedures performed at our institution with the aid of thoracic physician operated ultrasound and we show that in the Australian public health system, it remains safe and effective.